Toxoplasma gondii seropositivity and serointensity and cognitive function in adults. - Shawn D Gale; Lance D Erickson; Evan L Thacker; Elizabeth L Mitchell; Bruce L Brown; Dawson W Hedges (Public Library of Science (PLoS), 2020)
Infecting approximately one-third of the world's human population, Toxoplasma gondii has been associated with cognitive function. Here, we sought to further characterize the association between Toxoplasma gondii and cognitive function in a community sample of adults aged approximately 40 to70 years. Using adjusted linear regression models, we found associations of Toxoplasma gondii seropositivity with worse reasoning (b = -.192, p < .05) and matrix pattern completion (b = -.681, p < .01), of higher anti-Toxoplasma gondii p22 antibody levels with worse reasoning (b = -.078, p < .01) and slower Trails (numeric) performance (b = 5.962, p < .05), of higher anti-Toxoplasma gondii sag1 levels with worse reasoning (b = -.081, p < .05) and worse matrix pattern completion (b = -.217, p < .05), and of higher mean of the anti-Toxoplasma gondii p22 and sag1 levels with worse reasoning (b = -.112, p < .05), slower Trails (numeric) performance (b = 9.195, p < .05), and worse matrix pattern completion (b = -.245, p < .05). Neither age nor educational attainment moderated associations between the measures of Toxoplasma gondii seropositivity or serointensity. Sex, however, moderated the association between the sag1 titer and digit-symbol substitution and the association between the mean of the p22 and sag1 levels and digit-symbol substitution, and income moderated the association between Toxoplasma gondii seropositivity and numeric memory and the association between the p22 level and symbol-digit substitution. Based on the available neuropsychological tasks in this study, Toxoplasma gondii seropositivity and serointensity were associated with some aspects of poorer executive function in adults.